Resolution of Famous Trademark Disputes in Indonesia (Study of Supreme Court Decision Number 58/Pdt.Sus‐Merek/2020/PN.Niaga.Jkt.Pst) - Rizqi Aulia Amanda; Hanifah Febriani (Universitas Muhammadiyah Surakarta, 2023)
Brand is an identification or characteristic that is able to describe individuality and guarantee the quality of goods and services produced in business. Brands are very meaningful in business. Brands in certain goods or services that are well‐known and selling well in the market often encourage entrepreneurs and other producers to spur their product results so they can compete with other wellknown products, even though unhealthy disputes often arise. Brand ownership is recognized when the mark is registered with DJKI. Even though this has been regulated, violations of trademark rights still occur. This research will discuss the settlement of trademark disputes between Nintendo Co,. Ltd as the plaintiff against PT Cardolestari Indonesia as the defendant, based on Law no. 20/2016. This study uses normative legal research methods carried out through secondary data collection, with primary and secondary legal materials and with the Nintendo Co. Case approach. Ltd against PT Cardolestari Indonesia. From the results of the research it was found that legal protection in handling disputes over registered trademarks is a legal principle of